Serial Posterior Cranial Vault Distraction for the Treatment of Complex Craniosynostosis. Issue 1 (January 2021) - Veith, Jacob; Johns, Dana; Mehta, Sagar T.; Hosein, Ray; Tuncer, Fatma Betul; Tyrell, Richard; Kestle, John R.W.; Siddiqi, Faizi; Gociman, Barbu
Abstract : Abstract: Posterior cranial vault distraction is an important modality in the management of craniosynostosis. This surgical technique increases intracranial volume and improves cranial aesthetics. A single procedure is often inadequate in patients with complex multisuture craniosynostosis, as some will go on to develop intracranial hypertension despite the operation. Considering the negative effects of intracranial hypertension, some patients may warrant 2 planned distractions to prevent this scenario from ever occurring. Three patients with complex multiple-suture synostosis and severe intracranial volume restriction (occipital frontal head circumferences [OFCs] <1st percentile) were treated with 2 planned serial posterior cranial vault distractions at the institution between 2013 and 2018. Demographics, intraoperative data, and postoperative distraction data were collected. The OFC was recorded pre- and postdistraction, at 3- and 6-month follow-up appointments. Patients had a corrected average age of 18 weeks at the time of their initial procedure. There was an average of 38 weeks between the end of consolidation and the time for their 2nd distraction procedure. There was an average age of 79 weeks at the time of the 2nd procedure. All patients had a substantial increase in OFC and improvement of the posterior calvarium shape. The average increase in OFC was 5.2 cm after first distraction and 4.3 cm after 2nd distraction. No postoperative complications were encountered. Planned serial posterior cranial vault distraction is a safe and effective strategy for increasing intracranial volume, improving aesthetic appearance, and preventing the consequences of intracranial hypertension in patients with multisuture craniosynostosis and severe intracranial volume restriction. Abstract : Supplemental Digital Content is available in the text